Pengaruh Struktur Kepemilikan, Kebijakan Keuangan, dan Intangible Asset Value Terhadap Nilai Perusahaan ( Studi Empiris Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2011-2014 ) - Wahyuningsih, Winda; , Dr. Triyono, SE., M.Si (2016)
This study aimed to analyze the effect of ownership structure, financial policy, and intangible asset value to the company's value of the manufacturing companies that are listed in the Indonesia Stock Exchange in 2011-2014. The population used in this study is manufacturing companies that are listed in the Indonesia Stock Exchange (BEI) in 2011-2014. The sampling techniques is using purposive sampling method in accordance with predetermined criteria. The number of samples collected are 41 corporate data. The collected data were analyzed using data analysis conducted prior classic assumption test before hypothesis test. Testing in this study using multiple linear regression analysis with t-test, f-test, and the coefficient of determination. The result of this study indicate that the debt policy (DER) and intangible asset value (INTAV) have an effect on the value of the company, while the managerial ownership (KM), the institutional ownership (KI), the dividend policy (DPR) have no effect on the value of the company. Keywords: managerial ownership, institutional ownership, dividend policy, debt policy, intangible asset value.